Genetic abnormalities in myelodysplasia and secondary acute myeloid leukemia: impact on outcome of stem cell transplantation - Yoshizato, Tetsuichi (Blood, 2017)
Genetic alterations, including mutations and copy-number alterations, are central to the pathogenesis of myelodysplastic syndromes and related diseases (myelodysplasia), but their roles in allogeneic stem cell transplantation have not fully been studied in a large cohort of patients. We enrolled 797 patients who had been diagnosed with myelodysplasia at initial presentation and received transplantation via the Japan Marrow Donor Program. Targeted-capture sequencing was performed to identify mutations in 69 genes, together with copy-number alterations, whose effects on transplantation outcomes were investigated. We identified 1776 mutations and 927 abnormal copy segments among 617 patients (77.4%). In multivariate modeling using Cox proportional-hazards regression, genetic factors explained 30% of the total hazards for overall survival; clinical characteristics accounted for 70% of risk. TP53 and RAS-pathway mutations, together with complex karyotype (CK) as detected by conventional cytogenetics and/or sequencing-based analysis, negatively affected posttransplant survival independently of clinical factors. Regardless of disease subtype, TP53-mutated patients with CK were characterized by unique genetic features and associated with an extremely poor survival with frequent early relapse, whereas outcomes were substantially better in TP53-mutated patients without CK. By contrast, the effects of RAS-pathway mutations depended on disease subtype and were confined to myelodysplastic/myeloproliferative neoplasms (MDS/MPNs). Our results suggest that TP53 and RAS-pathway mutations predicted a dismal prognosis, when associated with CK and MDS/MPNs, respectively. However, for patients with mutated TP53 or CK alone, long-term survival could be obtained with transplantation. Clinical sequencing provides vital information for accurate prognostication in transplantation.